2021
DOI: 10.1097/aco.0000000000000974
|View full text |Cite
|
Sign up to set email alerts
|

The Do Not Resuscitate (DNR) order in the perioperative setting: practical considerations

Abstract: Purpose of review Addressing patients’ Do Not Resuscitate (DNR) status in the perioperative setting is important for shared patient decision-making. Although the inherently resuscitative nature of anesthesia and surgery may pose an ethical quandary for clinicians tasked with caring for the patient, anesthesiologist-led efforts need to evaluate all aspects of the DNR order and operative procedures. Recent findings Approximately 15% of patients undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…NIRS failure rate up to 40% is described due to patient's discomfort and refusal to continue treatment in most cases [24]. In a recent survey [25] conducted on patients without limitation of care, assisted by NIRS, it is reported that patient's experience was unpleasant due to intolerance of the interface used and the lack of relief from respiratory distress.…”
Section: Non-invasive Respiratory Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…NIRS failure rate up to 40% is described due to patient's discomfort and refusal to continue treatment in most cases [24]. In a recent survey [25] conducted on patients without limitation of care, assisted by NIRS, it is reported that patient's experience was unpleasant due to intolerance of the interface used and the lack of relief from respiratory distress.…”
Section: Non-invasive Respiratory Supportmentioning
confidence: 99%
“…In this case, it is essential to review, when possible, with the patient, all the advance directives in place before proceeding with any therapeutic action, to make clear what interventions may be accepted and which refused. The delicate relationship between perioperative care and do-not-resuscitate order is the matter of intense debate and investigation in the ethical field [24]. The same cannot be said for specific advance directives, such as a DNI order, wherein the indications are not so clear and detailed.…”
Section: Other Ethical Aspectsmentioning
confidence: 99%
“…The CMO operationalizes patients' preferences in a brief form that facilitates quick decisions which are important in community settings and preoperative situations. 35 Following adequate discussion of their potential benefits and harms, additional orders can also be added for this purpose, e.g., Do-Not-Hospitalize or Do-Not Operate-Unless. This is consistent with the recommendation that a medical order should clearly outline what treatments are appropriate for a patient, and those that should be withheld.…”
Section: Creating the Ordermentioning
confidence: 99%